2004
DOI: 10.1093/bmb/ldh043
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal meningitis

Abstract: Cryptococcal meningitis is a common opportunistic infection in AIDS patients, particularly in Southeast Asia and Africa. Cases also occur in patients with other forms of immunosupression and in apparently immunocompetent individuals. Mortality from HIV-associated cryptococcal meningitis remains high (10-30%), even in developed countries, because of the inadequacy of current antifungal drugs and the complication of raised intracranial pressure. In cohorts of HIV-infected patients from sub-Saharan Africa, crypto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
319
0
34

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 335 publications
(366 citation statements)
references
References 68 publications
13
319
0
34
Order By: Relevance
“…Clinical observations have revealed that patients infected with C. gattii have a higher rate of hydrocephalus requiring shunting [18]. The mechanism is hypothesized to be the obstruction of CSF outflow by to a large burden of yeasts and polysaccharide plugging the arachnoid granulations.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations have revealed that patients infected with C. gattii have a higher rate of hydrocephalus requiring shunting [18]. The mechanism is hypothesized to be the obstruction of CSF outflow by to a large burden of yeasts and polysaccharide plugging the arachnoid granulations.…”
Section: Discussionmentioning
confidence: 99%
“…1 CM has become the leading cause of community-acquired meningitis (ahead of tuberculous and bacterial meningitis), and if not treated correctly, has a significant mortality. 2 In 2009, the global incidence of CM ranged from 0.04-12% per year among persons living with human immunodeficiency virus (HIV)/AIDS. Sub-Saharan Africa had the highest yearly burden estimate (median incidence 3.2%, 720 000 cases, range 144 000-1.3 million).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenic fungus Cryptococcus neoformans is one of two species of cryptococci commonly associated with infection in humans (2,6). Unifying characteristics of the pathogenic cryptococci include the production of a polysaccharide capsule, the ability to form melanin pigments through the activity of the multicopper oxidase laccase, and the ability to adapt to and thrive at mammalian host temperature.…”
mentioning
confidence: 99%